2020
DOI: 10.11646/zootaxa.4851.2.11
|View full text |Cite
|
Sign up to set email alerts
|

New records and two new species of Xiphocentron Brauer 1870 (Trichoptera, Xiphocentronidae) from southern Atlantic Forest, Brazil

Abstract: Xiphocentron is the most species-rich genus of the pantropical family Xiphocentronidae. Among its five subgenera, Antillotrichia is the most diverse and the only one to occur in South America and Antilles. In the present study, two new species of Xiphocentron (Antillotrichia) are described from southern Atlantic Forest, Brazil. Xiphocentron gwarakeraba sp. nov. is diagnosed by the very elongate inferior appendage not bearing spines and with a simple mesal sclerite; X. muelleri sp. nov. is diagnosed by the infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 892 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…For the description of wing venation, we followed Vilarino and Bispo (2020). For the study of the internal structure of the male genitalia, we put the entire adults or an abdomen into a small container with a solution of 10% of KOH, and then kept on a hot plate at 100 °C for 10 minutes, in order to clear the genitalia.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the description of wing venation, we followed Vilarino and Bispo (2020). For the study of the internal structure of the male genitalia, we put the entire adults or an abdomen into a small container with a solution of 10% of KOH, and then kept on a hot plate at 100 °C for 10 minutes, in order to clear the genitalia.…”
Section: Methodsmentioning
confidence: 99%
“…The Xiphocentronidae are organized in two subfamilies: Proxiphocentroninae Schmid, 1982and Xiphocentroninae Schmid, 1982(Vilarino et al 2018. The genus Xiphocentron Brauer, 1870 includes the majority of the species of the family, with 53 extant species and two subspecies widely distributed in the Neotropics (Holzenthal and Calor 2017;Vilarino and Bispo 2020) and one fossil species described from Chiapas, Mexico (Wichard et al 2006). The genus Xiphocentron is subdivided into five subgenera: Glyphocentron Schmid, 1982, Rhamphocentron Schmid, 1982, Sphagocentron Schmid, 1982, Xiphocentron Schmid,1982, and Antillotrichia Banks, 1941(Holzenthal and Calor 2017Vilarino et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…urn:lsid:zoobank.org:pub:C6F8E502-3898-44A6-968A-F302C8521F9D (Malm et al 2013;Thomas et al 2020) and are now found in small streams and waterfalls throughout the tropical zone, with a high diversity in Mesoamerica and Southeast Asia (Vilarino & Bispo 2020). Unlike most Trichoptera, adults of Xiphocentronidae are active during the day (Flint 1968;Schmid 1982) and their larvae have semi-terrestrial habits, living in serpentine silken galleries often built outside the water over moist rocks and logs, feeding on microalgae and surface debris (Sturm 1960;Muñoz-Quesada & Holzenthal 1997;Pes et al 2013).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…This family is represented in the Neotropics by three genera and over 62 species (Vilarino & Bispo 2020). In Panama, all three Neotropical genera are known: (Caenocentron Schmid 1982, Machairocentron Schmid 1982, and Xiphocentron Brauer 1870, within which are distributed eight species.…”
Section: Family Xiphocentronidaementioning
confidence: 99%